Influence of Focal Length Position of Focusing Lens on Plywood Discoloration Under Different Modes of CO2 Laser Engraving - Zhivko Gochev; Pavlin Vichev (Drvna Industrija, 2025)
This paper presents the results of a study of the laser engraving process on birch plywood samples. The influence of the focal distance of the focusing lens at different positions relative to the surface of the material on the discoloration of plywood samples, at different power and scanning speed of a CO2 laser beam, was investigated. The change in the color shades of the plywood was studied with an LS173 calorimeter. For this research, the following parameters were used: ZnSe lens with focal length F = 50.8 mm; the position of the focal plane of the focusing lens relative to the surface of the material ΔF = 4, 6, and 8 mm; laser beam power P = 4.0; 5.6 and 7.2 W; feed rate of the laser beam Vf = 250; 260 and 270 mm/s. The color shade difference of the plywood samples was measured in the L*, a* and b* color space. The results allow to define modes for surface treatment with laser beam in the construction of complex graphic images on plywood products.